El cariotipo de Chaetanthera linearis Poepp. (Asteraceae) - Baeza, Carlos M.; Ruiz, Eduardo; Novoa, Patricio; Negritto, María A. (Gayana Botánica, 2010)
The karyotype of Chaetanthera linearis var. linearis from Chile was examined. The species has 2n = 2x = 22 chromosomes, with 9m + 1st + 1 st-sat chromosomes. The reported karyotype is symmetric (AsK % = 58.0, TF % = 42.0 and Syi % = 72.4). The karyotype of this species was compared with Ch. microphylla var. microphylla a very similar species in morphology and distribution to Ch. linearis var. linearis, but with clearly differentiated karyotype.